Rupturas e permanências no processo de emancipação da mulher trabalhadora rural: análise da concessão de crédito no contexto do PRONAF na Baixada Ocidental maranhense - Santos, Nilma Angélica dos (2017)
This paper analyzes the conditions of access of rural female workers to the productive credit granted by the National Program for Strengthening Family Agriculture (PRONAF) in the Baixada Ocidental Maranhense. It is an effort to analyze the quality and effectiveness of this access based on the conception of women's financial autonomy - understood as the capacity to freely manage their means of production - and on public policies aimed at the sustainable development of family agriculture. In order to do so, it focuses on the multiple dimensions of the theme, such as gender relations, agrarian issues and public policies. In addition, it analyzes the perception of these women about the process of domination / exploitation in which they are inserted through their gender condition and their socioeconomic position, investigating what possibilities open to improving their access to rural credit policy in order to contribute With its social emancipation - understood as the overcoming of the impediments placed to its free expression and association as a social being and to self-determination and representation as a human being (MARX, 1844). In order to grasp the totality of the multiple determinations of the phenomenon, the dialectical historical materialist method was chosen, given its possibilities of understanding reality in its dynamics and concreteness (as a theoretical framework that understands reality in a dynamic way and pervaded by aspects , Economic, political, ideological, cultural, environmental). With the effort to approach the object of study in order to identify how the problem is contextualized and based on a given reality, the qualitative analysis of the facts observed with quantitative data on the number of beneficiaries was complemented, Financing values and numbers referring to the variations occurred in family agricultural production in the municipalities surveyed during the determined time interval.